1990
DOI: 10.1104/pp.93.2.642
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Nitrate Transport in Maize Roots, and Kinetics of Influx, Measured with Nitrogen-13

Abstract: Unlike phosphate or potassium transport, uptake of nitrate by roots is induced, in part, by contact with the substrate ion.Plasmalemma influx of 13N-labeled nitrate in maize roots was studied in relation to induction of the uptake system, and the influence of short-term N starvation. Maize (Zea mays) roots not previously exposed to nitrate had a constitutive transport system (state 1), but influx increased 250% during six hours of contact with 100 micromolar nitrate, by which time the transport mechanism appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
65
0
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 21 publications
15
65
0
3
Order By: Relevance
“…This model conformed best with the measured data with regard to the obtained standard errors (data not shown) and the fitting of curves to the means of uptake rates (Fig. 3) Aslam et al 1992), but lower than those found in maize (24 mmol m -3 , Hole et al 1990), in wheat (27 mmol m -3 , Goyal & Huffaker 1986b) and in Arabidopsis (40 mmol m -3 , Doddema & Telkamp 1979) or in excised barley roots in earlier reports (110 mmol m -3 , Rao & Rains 1976a). Similar agreements were found for the 13 N-NO 3 -influx (Lee & Drew 1986: 14 mmol m -3 ;Siddiqi et al 1990: between 30 and 79 mmol m -3 depending on the N status of the plants).…”
Section: Kinetic Parametersmentioning
confidence: 50%
“…This model conformed best with the measured data with regard to the obtained standard errors (data not shown) and the fitting of curves to the means of uptake rates (Fig. 3) Aslam et al 1992), but lower than those found in maize (24 mmol m -3 , Hole et al 1990), in wheat (27 mmol m -3 , Goyal & Huffaker 1986b) and in Arabidopsis (40 mmol m -3 , Doddema & Telkamp 1979) or in excised barley roots in earlier reports (110 mmol m -3 , Rao & Rains 1976a). Similar agreements were found for the 13 N-NO 3 -influx (Lee & Drew 1986: 14 mmol m -3 ;Siddiqi et al 1990: between 30 and 79 mmol m -3 depending on the N status of the plants).…”
Section: Kinetic Parametersmentioning
confidence: 50%
“…Furthermore, AtNrt2.1 transcript level is strongly increased by dark-to-light transition and Suc supply to the roots, suggesting that it is also under control by photosynthetic activity of the shoots . Thus, regulation of AtNrt2.1 expression is very similar to that of the HATS for NO 3 Ϫ , which is inducible by NO 3 Ϫ (Jackson et al, 1973;Siddiqi et al, 1989), repressed by high nitrogen status of the plant and nitrogen metabolites (Hole et al, 1990;Lee et al, 1992;Muller and Touraine, 1992), and stimulated by photosynthesis and sugars (Delhon et al, 1996;Lejay et al, 1999). The demonstration that plant NRT2 proteins do have a transport activity on their own is still lacking, possibly because the actual transporter requires the presence of another protein, encoded by the Nar2-like gene (Zhou et al, 2000).…”
mentioning
confidence: 84%
“…Nitrogen starvation or nitrogen-limiting conditions lead to a marked increase in the root capacity to take up NO 3 Ϫ or NH 4 ϩ (Lee and Rudge 1986), a response that is mostly due to the stimulation of the HATSmediated influx of the two ions (Morgan and Jackson, 1988;Hole et al, 1990;Lee, 1993;Wang et al, 1993), and is associated in Arabidopsis with a strong increase in the expression of the NO 3 Ϫ and NH 4 ϩ transporter genes AtNrt2.1 and AtAmt1.1 (Gazzarrini et al, 1999;Lejay et al, 1999). This regulation is thought to be due to repression of NO 3 Ϫ and NH 4 ϩ transporters by reduced nitrogen metabolites accumulating in the tissues under satiety conditions (Jackson et al, 1986;Clarkson and Lü ttge, 1991;Lee et al, 1992;Muller and Touraine, 1992).…”
Section: The Atnrt2 Mutant Lacks the Hats Component Under Feedback Comentioning
confidence: 99%
“…Classically, the HATS for NO 3 3 is believed to be constituted of at least two separate transport systems, a cHATS and a NO 3 3 -inducible iHATS [1,3,4]. The iHATS is generally reported to be much more active than the cHATS in NO 3 3 -induced plants [30,31]. Thus, it is tempting to postulate that the large di¡erence in V max of the HATS between the wild-type and the mutant is due to the absence of the iHATS in the latter genotype.…”
Section: Isolation Of An Atnrt2 T-dna Insertion Mutantmentioning
confidence: 99%